Collaboration of Educational Institutions and Industry: Realizing Teaching Factory for Dedicated and Integrity-driven Human Resources - Puspitasari, Fantika Febry (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to describe and analyze the process of building an electrical engineering teaching factory at SMKN 1 Paringin. This study uses a qualitative approach with a case study design. Data collection techniques were conducted through interviews, observations, and documentation. Data analysis began with condensing interview and document data, then sorting it according to the research objectives. The sorted data is presented in narrative form according to the research objectives. The narrative of the research data is summarized based on the discussion points. Data validity checks were conducted using source triangulation and technique triangulation. The results show that SMKN 1 Paringin and PT Adaro collaborated to develop productive and dedicated teachers for the teaching factory. Teachers were trained to create block schedules and job sheets based on processes and outcomes, applying teaching factory standards, quality control, and community service. The community service program at SMKN 1 Paringin is an attractive model because it focuses on developing workforce skills and altruistic aspects. This research supports further development in other vocational schools in Indonesia, especially in Centers of Excellence vocational schools, to sustainably enhance their benefits for industries and communities.